2018
DOI: 10.1177/0033354918776641
|View full text |Cite
|
Sign up to set email alerts
|

A Surveillance-Based Hepatitis C Care Cascade, New York City, 2017

Abstract: A substantial gap exists between confirming HCV infection and initiating treatment, even in the era of direct-acting antivirals. Using this cascade, we will monitor progress in improved treatment and cure of HCV in NYC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
10
2
Order By: Relevance
“…LTC was 40.6% in our study, lower than other integrated health systems that utilize best practice interventions and patient navigators [14, 15, 17, 18]. We found that 34.6% of those LTC began DAA therapy, which is higher than in some studies [2426] but not others [27]. Whether this rate was due to our patients linking early or that greater than 90% of our patients had insurance is unclear.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…LTC was 40.6% in our study, lower than other integrated health systems that utilize best practice interventions and patient navigators [14, 15, 17, 18]. We found that 34.6% of those LTC began DAA therapy, which is higher than in some studies [2426] but not others [27]. Whether this rate was due to our patients linking early or that greater than 90% of our patients had insurance is unclear.…”
Section: Discussioncontrasting
confidence: 70%
“…However, it must be noted that due to our low LTC, there was not a large cohort to assess for initiation or completion of DAA therapy. Among PWID, 27.8% achieved LTC, lower than reported elsewhere [27, 28]. However, 40% were started on DAA therapy, which is higher than that found in other reports [27].…”
Section: Discussioncontrasting
confidence: 58%
“…With the high efficacy of new direct antiviral agents (DAAs), in Brazil, the challenge exists in need to identify and treat infected patients [19]. However, the lack of an efficient cascade of care for chronic HCV infection in Brazil hinders the diagnosis of the disease and access to treatment, which are the most critical factors for eliminating HCV infection and reducing HCV-related mortality [20]. This descriptive, observational, cross-sectional study aimed to evaluate the efficiency of the cascade of care for HCV-positive patients among people aged > 40 years in Brasilia, Brazil.…”
mentioning
confidence: 99%
“…Access to HCV treatment in the community has improved in the DAA era, with 52% of those with a positive HCV RNA test in NYC between 2014 and 2017 initiating treatment [7] . However, ongoing barriers to care limit progression through the HCV care cascade for many incarcerated individuals [ 3 , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…In the community, the HCV care cascade has improved during the direct-acting antiviral (DAA) treatment era [ 6 , 7 ], but incarcerated populations still face barriers to diagnosis and care [8] , [9] , [10] . With 10.7 million admissions nationally in 2018, US jails are primarily remand settings with high turnover (mean length of stay was 25 days) [11] .…”
Section: Introductionmentioning
confidence: 99%